1996
DOI: 10.1177/135245859600100405
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Imaging of Epilepsy in Multiple Sclerosis: A Case Control Study. Implications for Treatment Trials with 4-Aminopyridine

Abstract: A case-control study of epilepsy in multiple sclerosis (MS) is presented using magnetic resonance (MR) imaging to semiquantitatively assess cortical-subcortical lesion load. In this sample of 13 pairs of cases with MS and epilepsy and controls with MS without epilepsy we found statistically higher cumulated cortical-subcortical lesion loads in the cases than in the controls (Wilcoxon, P=0.036). Total lesion loads (cortical-subcortical plus deep white matter loads) did not differ significantly (P > 0.1) betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 9 publications
0
21
0
Order By: Relevance
“…In a case-control study Truyen et al [83] found a significantly higher cortical-subcortical lesion load in MS patients suffering from epileptic seizures than in those without seizures. Deep white matter lesions did not differ between cases and controls.…”
Section: S Classification Of Seizures and Epilepsies In Msmentioning
confidence: 96%
See 1 more Smart Citation
“…In a case-control study Truyen et al [83] found a significantly higher cortical-subcortical lesion load in MS patients suffering from epileptic seizures than in those without seizures. Deep white matter lesions did not differ between cases and controls.…”
Section: S Classification Of Seizures and Epilepsies In Msmentioning
confidence: 96%
“…In this context it has been argued that patients with a high load of cortical and subcortical lesions in MRI should be excluded from drug trials with remedies having a known potential to lower the seizure threshold [83]. While reasonable, this suggestion is based on the presumption that local factors and pharmacological effects are additive in their potential to cause seizures.…”
Section: S Correlation To Severity and Course Of Msmentioning
confidence: 99%
“…Prevalence numbers of seizures in MS patients range from 0.5% to 8.3%, which is roughly three times higher than in the general population (Ghezzi et al, 1990;Moreau et al, 1998;Sokic et al, 2001;Nyquist et al, 2001;Gambardella et al, 2003;Poser and Brinar, 2003;Koch et al, 2008;Martinez-Juarez et al, 2009;Catenoix et al, 2011;Uribe-San-Martin et al, 2014). Most of the more dated research shows inconsistent results of the relation between (sub)cortical lesions and epileptic seizures (Ghezzi et al, 1990;Thompson et al, 1993;Truyen et al, 1996;Moreau et al, 1998;Sokic et al, 2001;Gambardella et al, 2003;Poser and Brinar, 2003;Uribe-San-Martin et al, 2014). Although tumefactive WM lesions with cortical compression were more likely to be related to seizure onset in these studies, the epileptogenic potential of smaller cortical lesions was less evident, and the electro-encephalography (EEG) defined onset zone frequently did not match lesion location (Ghezzi et al, 1990;Thompson et al, 1993;Truyen et al, 1996;Moreau et al, 1998;Sokic et al, 2001;Gambardella et al, 2003;Poser and Brinar, 2003;Uribe-San-Martin et al, 2014).…”
Section: Epileptic Seizures In Patients With Multiple Sclerosismentioning
confidence: 99%
“…In the second half of the 20th century, it became clear that some clinical signs of MS, such as cognitive impairment (Benedict et al, 2004Morgen et al, 2006) and epileptic seizures (Ghezzi et al, 1990;Thompson et al, 1993;Truyen et al, 1996;Moreau et al, 1998;Sokic et al, 2001;Gambardella et al, 2003;Poser and Brinar, 2003;Uribe-San-Martin et al, 2014), could not be explained with WM pathology alone. Development of more advanced histopathological and magnetic resonance imaging (MRI) techniques subsequently led to more insights into GM pathology in MS.…”
mentioning
confidence: 99%
“…Moreover, MS may present with epilepsy [6,7] and, in some cases, seizures may be the only manifestation of a MS relapse [8].Whether the two diseases occur accidentally,or MS non-specifically triggers a latent proneness to epilepsy, or MS is the actual causation of seizures is still debated [9]. Studies with conventional magnetic resonance (MR) sequences have suggested a possible correlation between the presence of cortical-juxtacortical MS lesions and epileptic seizures in MS [10,11].…”
Section: Introductionmentioning
confidence: 99%